Book Review of Zeavin's The Distance Cure: A History of Teletherapy - Strong, Tom (Canadian Journal of Counselling and Psychotherapy, 2022)
Teletherapy refers to a range of mental health services facilitated at a distance by the use of different communications media. In The Distance Cure, Hannah Zeavin critically examines the history of teletherapy as a scholar of communications, culture, and technology. Her analyses show how cultural notions of what is therapeutic as well as practices and relations between clients and counsellors have been transformed by changes in media.